Nutritional considerations for the female vegan athlete. - Schoenfeld, M. L. (Strength and Conditioning Journal, 2020)
According to the top trends in prepared foods 2017 market research report, the number of U.S. consumers following a vegan lifestyle has jumped from 1% of the population in 2014 to 6% of the population in 2017. It is therefore a reality that many female athletes may be considering or following a vegan lifestyle. Although macronutrient and micronutrient needs can certainly be met on a meat-free diet, understanding how to execute a nutritionally sound vegan diet is key. This article will discuss the vegan diet, as it pertains to the female athlete.